Palladium catalyzed asymmetric hydrophosphination of α,β- and α,β,γ,δ-unsaturated malonate esters : efficient control of reactivity, stereo- and regio-selectivity - Leung, Pak-Hing (2015)
Both PC-cyclometalated and PCP-pincer type palladium catalysts have recently been found to be robust and efficacious catalysts for the asymmetric P–H addition reaction involving activated olefins. Our studies on the asymmetric P–H addition of diphenylphosphine to malonate ester and α,β,γ,δ-alkylidenemalonate ester revealed for the first time that the catalyst choice can have a dramatic impact in terms of reactivity as well as regio- and stereo-control for this asymmetric hydrofunctionalization reaction. Besides showing significantly contrasting reactivity and stereoselectivity in the hydrophosphination reaction involving malonate ester, in the case of α,β,γ,δ-alkylidenemalonate ester, a novel regiodivergent method was developed with the 1,4-adduct being obtained exclusively with the PC-catalyst while the pincer catalyst produced only the 1,6-adduct.